Do Pet Cats Deserve the Disproportionate Blame for Wildlife Predation Compared to Pet Dogs? - Franklin, Michael; Rand, Jacquie; Marston, Linda; Morton, John (Frontiers in Veterinary Science, 2021)
Concerns about the impact of pet dogs and cats on native wildlife populations has shaped pet control legislation, despite there being scant research of their impact in urban areas. Using an online questionnaire, we obtained data from 662 Australian dog and cat owners who had observed their pets capture prey in the previous 6 months. Of the pets observed to catch prey, dogs caught a median of 2 mammals, 2 birds, 2 reptiles and 3 amphibians, whereas cats caught a median of 3 mammals, 2 birds, 4 reptiles and 2 amphibians. Of mammals caught by dogs and cats, 88% and 93% respectively were identifiable as introduced mice, rats and rabbits. Of pets that caught prey, a substantial proportion caught native animals (62% of dogs and 47% of cats). However, median numbers of native animals caught per dog (2) or cat (3) over 6 months were low. Small skinks and lizards comprised the greatest proportion for dogs and cats, but dogs also caught larger native prey (e.g., possums, kangaroos and wallabies). Most birds caught by dogs and cats were common or introduced (dogs: crested pigeons, lorikeets; cats: noisy miners, rosellas). To design measures that will effectively protect Australia’s native wildlife, thorough understanding of the role dogs and cats play in Australian urban ecosystems is required. These findings can inform that understanding, and assist with development of management strategies for urban dogs and cats, and as well as directing resources to efforts that will most protect urban wildlife.